The preparation of microfluidic architecture with monolithic materials using a dual porous silica structure. Issue 22 (23rd August 2017) - Birch, Christopher; Esfahani, Mohammad Mehdi Nasr; Shaw, Kirsty J; Kemp, Cordula; Haswell, Stephen James; Dyer, Charlotte
Abstract: A microfluidic device (MD) has been developed which features a porous silica (PS) monolithic disk synthesized from tetramethyl orthosilicate, incorporated into the device post‐fabrication and sealed in place with a second PS monolithic layer, synthesized from potassium silicate. This dual porous silica (DPS) structure provides a pathway for sample introduction to the MD and offers an ideal platform for solid phase extraction (SPE) methodologies which can be rapidly and efficiently integrated into a chip‐based format. All silica disk manufacture and functionalization was carried out in batch to provide a readily scalable method of production. Application of this design for processing samples was demonstrated using two alternative nucleic acid purification chemistries, yielding polymerase chain reaction amplifiable DNA extracted from 150 μL of human urine in less than 35 min. It is proposed that this DPS system could be further developed for a diverse range of chip‐based SPE applications, providing an interface facilitating sample delivery and enabling SPE on‐chip. Furthermore, to the author's knowledge it is the first reporting of two different types of PS amalgamated in a single MD.